Decoding the Neural Dynamics of Headed Syntactic Structure Building - Zhao 赵隽元, Junyuan; Gao 高睿敏, Ruimin; Brennan, Jonathan R (The Journal of neuroscience, 2025)
The brain builds hierarchical phrases during language comprehension; however, the details and dynamics of the phrase-building process remain underspecified. This study directly probes whether the neural code of verb phrases involves reactivating the syntactic property of a key subcomponent (the "head" verb). To this end, we train a part-of-speech sliding-window verb/adverb decoder on EEG signals recorded while 30 participants read sentences in a controlled experiment. The decoder reaches above-chance performance that is spatiotemporally consistent and generalizes to unseen data across sentence positions. Applying the decoder to held-out data yields predicted activation levels for the verbal "head" of a verb phrase at a distant nonhead word (adverb); the critical adverb appeared either at the end of a verb phrase or at a sequentially and lexically matched position with no verb phrase boundary. There is stronger verb activation beginning at ∼600 milliseconds at the critical adverb when it appears at a verb phrase boundary; this effect is not modulated by the strength of conceptual association nor does it reflect word predictability. Time-locked analyses additionally reveal a negativity waveform component and increased beta-delta inter-trial phase coherence, both previously linked to linguistic composition, in a similar time window. With a novel application of neural decoding, our findings delineate the dynamics by which the brain encodes phrasal representations by, in part, reactivating the representation of key subcomponents. We thus establish a link between cognitive accounts of phrasal representations and electrophysiological dynamics.